2016
DOI: 10.1016/j.jvs.2015.07.070
|View full text |Cite
|
Sign up to set email alerts
|

Intraspinal collateral circulation to the artery of Adamkiewicz detected with intra-arterial injected computed tomographic angiography

Abstract: When the intercostal and lumbar arteries are occluded by plaque or thrombus, spinal cord perfusion depends on collateral circulation. Some reports have demonstrated collateral circulation to the artery of Adamkiewicz via computed tomography and magnetic resonance angiographies. However, intraspinal collateral circulation to the artery of Adamkiewicz along the spinal cord has not been reported previously. Here, we report two patients with intraspinal collateral circulation to the artery of Adamkiewicz along the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The identification of collateral circulation in patients with risk factors of developing spinal cord ischemia is important for the surgical planning and prevention of neurological complications. 32 Among the most commonly used imaging modalities, the multi-detector row computed tomography (MDCT) seems to be the most promising, since it allows the three-dimensional reconstruction of images of the organ studied. In a recent study, collateral circulation could be identified by MDCT in 83% of patients with segmental artery occlusion in the artery originating from the artery of Adamkiewicz.…”
Section: Imaging Of Collateral Spinal Circulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of collateral circulation in patients with risk factors of developing spinal cord ischemia is important for the surgical planning and prevention of neurological complications. 32 Among the most commonly used imaging modalities, the multi-detector row computed tomography (MDCT) seems to be the most promising, since it allows the three-dimensional reconstruction of images of the organ studied. In a recent study, collateral circulation could be identified by MDCT in 83% of patients with segmental artery occlusion in the artery originating from the artery of Adamkiewicz.…”
Section: Imaging Of Collateral Spinal Circulationmentioning
confidence: 99%
“…In a recent study, collateral circulation could be identified by MDCT in 83% of patients with segmental artery occlusion in the artery originating from the artery of Adamkiewicz. 32 It was also reported that the use of other modalities, such as CT angiography (CTA) and magnetic resonance angiography (MRA), in order to check the collateral circulation to the Adamkiewicz artery through the intercostal artery, thoracodorsal artery, internal thoracic artery and inferior phrenic artery in patients with extensive degenerative thoracoabdominal aortic aneurysm, 32 reported detection rates between 67 to 93%. 7,33 However, the effectiveness is limited to the collateral paths exceeding the millimeter in diameter, and these also lack functional validation.…”
Section: Imaging Of Collateral Spinal Circulationmentioning
confidence: 99%
“…The second spinal branch participating on the blood supply of the thoracic and lumbar part is the artery of Adamkiewicz [45]. It is the largest spinal branch with variable level of its origin [46][47][48]. In 75% of cases, its origin is located at the level between ninth and twelfth thoracic segment, in 15% of cases between the fifth and eighth thoracic segment and in 10% of cases between the first and second lumbar segment [42,47].…”
Section: Thoracolumbar Part Of the Spinal Cordmentioning
confidence: 99%
“…It is the largest spinal branch with variable level of its origin [46][47][48]. In 75% of cases, its origin is located at the level between ninth and twelfth thoracic segment, in 15% of cases between the fifth and eighth thoracic segment and in 10% of cases between the first and second lumbar segment [42,47]. As left-sided artery, it was described in 80% of cases [49].…”
Section: Thoracolumbar Part Of the Spinal Cordmentioning
confidence: 99%
See 1 more Smart Citation